2015
DOI: 10.4081/itjm.2015.549
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of hypoglycemia in hospitalized patients

Abstract: Hypoglycemia is a very common problem, mostly in frail, severely ill, older hospitalized patients. Hypoglycemia has been implicated in the development of adverse clinical outcomes, including an increased mortality. Fear of iatrogenic hypoglycemia remains an obstacle to adequate inpatient glycemic control. It may be considered as a marker of disease, rather than cause in itself of undesirable events. Several factors, such as treatment with exogenous insulin, mismatch between insulin administration and meal inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Inpatient hypoglycaemia has been implicated in the development of adverse clinical outcomes, including increased mortality . One retrospective study in Spain showed that hypoglycaemia (blood glucose <3.9 mmol/l) in 154 510 people with diabetes during their hospitalization was associated with an increased likelihood of in‐hospital mortality [odds ratio (OR) 1.12, 95% CI 1.09–1.15] .…”
Section: Impact Of Inpatient Hypoglycaemiamentioning
confidence: 99%
“…Inpatient hypoglycaemia has been implicated in the development of adverse clinical outcomes, including increased mortality . One retrospective study in Spain showed that hypoglycaemia (blood glucose <3.9 mmol/l) in 154 510 people with diabetes during their hospitalization was associated with an increased likelihood of in‐hospital mortality [odds ratio (OR) 1.12, 95% CI 1.09–1.15] .…”
Section: Impact Of Inpatient Hypoglycaemiamentioning
confidence: 99%
“…Although only 7% experience a severe (Level 2) hypoglycemic episode, this rises to 26.9% of all patients with Type 1 diabetes with 185 people over the course of 1 week requiring injectable rescue treatment for their hypoglycemia. Inpatient hypoglycemia has been implicated in the development of adverse clinical and economic outcomes, including increased mortality [5][6][7], adverse cardiovascular outcomes [8,9] and increased duration of hospital stay [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although only 7% experience a severe (level 2) hypoglycemic episode, this rises to 26.9% of all patients with type 1 diabetes with 185 people over the course of 1 week requiring injectable rescue treatment for their hypoglycemia. Inpatient hypoglycemia has been implicated in the development of adverse clinical and economic outcomes, including increased mortality (5)(6)(7), adverse cardiovascular outcomes (8,9), and increased duration of hospital stay (6,10,11).…”
mentioning
confidence: 99%